Science Learning Based on Higher Order Thinking Skill and Its Supporting Components - Indah Annisa Diena; Insih Wilujeng; Prisca Arzita Perdana (Jurnal Penelitian Pendidikan IPA, 2023)
This article is a literature review article related to Higher Order Thinking Skill (HOTS)-based learning and its supporting components as one of the efforts in facing current educational challenges. The purpose of this article is to describe higher order thinking learning and it’s supporting components in successful learning. The data collection method used is literature study from various research reference sources and authors. The demand for increasing critical thinking skills can be overcome with real HOTS-based learning. Less than optimal achievement of HOTS-based learning objectives can occur due to lack of attention to supporting components in implementing HOTS-based learning. It is important to know and examine the supporting components in HOTS-based learning, including Teacher Competence, Facilities and Technology, Strategy, Student Motivation. This article provides an overview of how HOTS is applied in learning as well as the important components in the application of HOTS-based learning